Estimation of beach erosion using Joint Probability analysis with a morphological model. (15th November 2022) - Oo, Ye Htet; Vieira Da Silva, Guilherme; Zhang, Hong; Strauss, Darrell; Tomlinson, Rodger
Abstract: Resilience of a beach is often defined by return period ( RP ) of a designed storm. During extreme events some correlation exists between storm parameters, such as wave height ( H s ) and surge ( S ), and these parameters are also stochastic in nature. Thus, numerous combinations of H s and S occurs for the same level of RP . The objective of this study is to demonstrate if a same level of joint RP with different combination of H s and S would produce similar beach erosion, considering wave directions and orientation of coastline. To achieve this, a non-directional Joint Probability ( JP ) of storm H s and S is integrated with a morphological model. Three scenarios along a JP contour are selected and erosions are estimated. The selected JP scenarios are converted into a synthetic storm time-series for morphological simulations. The results demonstrated that JP with a high H s and low S scenario produced more erosion than other scenarios under constant direction. Regarding wave direction, for the same H s and S, the shore-normal wave direction produced highest erosion. Thus, shore-normal wave with high H s and low S produces the highest erosion than other combinations. This study demonstrates the importance of consideration various JP and wave directions in assessing resilience of a beach. Highlights: Integrate a joint probability method with a morphological model for extreme beach erosion analysis. Beach erosion can vary despite analysing the same joint return period of wave heights and water surface elevations. Wave heights are more important than water surface elevations for erosion on a wave dominated, micro-tidal coastline. A joint high wave height and low water surface elevation from shore normal direction produced the highest erosion.